Sistem Pengurusan Syukor Batik Menggunakan Aplikasi Mudah Alih - Che Mohd Zainudin, Wan Azra Balqis; Mohd Zainuri Saringat, (Applied Information Technology And Computer Science, 2021)
Syukor Batik Management System Using Mobile Application was developed for the purpose of helping the Syukor Batik store to manage sales activities and make it easier for their customers on making orders online. The existing manual system makes it difficult for the store to deal with customers through a live chat. This make burdens to the store in taking the order confirmation and customer’s payment because there are a few issues of late feedback, miscommunications and facing the issue of line disconnection. In addition, there are difficulties in recording accurate customer details, orders and sales records when they are only recorded the details in a notebook only. Next, the store also finds it difficult to update the current number of stocks to the customer. Because the number of stocks will always get change, and the current number of stock updates will be updated in a non-productive manner. Therefore, this Syukor Batik Management System Using Mobile Application was developed to assist the management of sales and records as well as to facilitate customers to make orders online. The system was developed in the Java programming language through Android Studio and Firebase software, based on the Object-oriented Systems Development Life Cycle (OOSDLC) model. The system is divided into two different but interconnected parts of the application. Every customer who wants to make orders online will use the part of mobile application. Meanwhile, to facilitate the management process, the store will use the website application to manage all sales and customer activities from the mobile application. The development of Batik Syukor Management System Using Mobile Application is expected to help the store in minimizing the weaknesses of sales management and existing problems by productively.